Interior design illustrated - Ching, Francis D.K.; Binggeli, Corky (Hoboken, New Jersey : John Wiley & Sons, Inc., 2012)
In this elegant new edition, Francis D.K. Ching takes integrated approach to interior design several steps further. A highly functional and beautifully illustrated work, Interior Design Illustrated, Third Edition offers a thorough introduction to interior design, addressing the architectural requirements of interior spaces and the details of furnishing and interior finishes. This new edition offers a concise and accessible presentation of important concepts for beginning designers, and experienced practitioners will appreciate its insightful and practical coverage of the relationship between building structures and interior spaces. A broad range of rich illustrations communicates visual information and ploughs fertile ground for creative ideas and inspiration. Featuring a full-color section on the role of color in interior design, as well as teaching resources available for the first time, Interior Design Illustrated, Third Edition provides new and expanded information on: Building codes, building information modeling, and sustainability--Indoor air quality, environmental systems, data/communication, and security systems--Translating functional needs into design decisions--Integrating environmental, health, safety, comfort, and conveyance systems into a building's structure and the design of its interior space--The functional, aesthetic, and expressive roles design elements can play in the development of three-dimensional space.
Interior Space -- Interior Design -- A Design Vocabulary -- Interior Building Elements -- Interior Environmental Systems -- Lighting and Acoustics -- Finish Materials -- Furnishings.
Includes bibliographical references and index.
Keywords: INTERIOR ARCHITECTURE; SPACE (ARCHITECTURE); INTERIOR DECORATION -- HISTORY -- 21ST CENTURY